2022
DOI: 10.54783/endlessjournal.v5i1.44
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Small and Medium Businesses Through the Utilization of Good Human Resources Management

Abstract: The importance of national development to improve the quality of people’s lives is quite essential because the welfare of its people indeed measures the development of a country. One of the steps to improve this welfare is to improve the quality of SMEs. Enhancing SMEs’ quality can be implemented by utilizing good human resource management. This study aims to see how the state operates human resource management to be able to increase SMEs owned by the community. This research will be carried out using various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…This study found a significant relationship between entrepreneurship training interventions and the performance of small-scale car companies in Ghana (Gyasi et al, 2020). SMEs can improve their human resources to become more competitive by implementing effective human resource management (Nugraha et al, 2022). Investments in employee development and training to improve the skills and knowledge of MSME players need to be made so that they can improve the performance of MSMEs (Yudistira et al, 2019).…”
Section: Human Capital Theorymentioning
confidence: 88%
“…This study found a significant relationship between entrepreneurship training interventions and the performance of small-scale car companies in Ghana (Gyasi et al, 2020). SMEs can improve their human resources to become more competitive by implementing effective human resource management (Nugraha et al, 2022). Investments in employee development and training to improve the skills and knowledge of MSME players need to be made so that they can improve the performance of MSMEs (Yudistira et al, 2019).…”
Section: Human Capital Theorymentioning
confidence: 88%
“…Dimana tercatat sekitar 74% UMKM belum mendapatkan akses pembiayaan sehingga sulit dalam mengembvangkan skala produksi. Disisi lain, rendahnya kualitas dan kapabilitas SDM pun menjadi permasalahan dalam upaya peningkatan UMKM, dimana banyak pelaku UMKM yang masih sulit dalam mengembangkan pemasaran, kurang inovatif, serta sulit mengurus perizinan serta belum mengelola laporan keuangan [7].…”
Section: Penulis Pertama Dkkunclassified